Editorial - Neves, Pedro Soares (Architecture Image Studies, 2023)
Welcome to the latest issue of AIS, where we delve into the fascinating realms of design, restoration, and place-making within the architectural landscape. In this edition, we present a collection of insightful articles that explore diverse aspects of architectural interventions, from urban parks to waterside mansions, participatory urban place-making, dog parks, and the evolution of interior design in 19th-century Ottoman architecture. As we navigate through these articles, it becomes evident that design, restoration, and place-making are not merely architectural endeavors but intricate processes that shape our interactions with the built environment. We hope this issue of AIS inspires architects, researchers, and enthusiasts alike to continue pushing the boundaries of creativity and functionality within the ever-evolving field of architecture.